Design for manufacturability how to use concurrent engineering to rapidly develop low-cost, high-quality products for lean production - Anderson, David M. (CRC Press, 2014)
"This book explains how to develop manufactured products right, the first time around. It describes how to reduce total cost, ramp to volume production on schedule, and increase production for demand so as not to limit growth. Most design for manufacturability books are written for design engineers and focus on the parts that determine 20% of the costs. This book focuses on designing products which determine 60% of the costs. This book is suitable for anyone involved in product development at manufacturing companies, including management, ownership, and the consultants that serve them"--Provided by publisher.